Kontribusi KSOP Kelas III Talang Duku Dalam Mendukung Efisiensi Operasional Transportasi Laut Nasional - Sipahutar, Yohana Avdes Roito; Kwartama, Agung (Jurnal Cakrawala Bahari, 2025)
This study aims to analyze the contribution of the Class III Talang Duku Port Authority (KSOP) in supporting the operational efficiency of national maritime transportation. As an important hub in the distribution of strategic commodities in Jambi Province, Talang Duku Port faces challengin terms of infrastructure limitations, river channel sedimentation, and suboptimal inter-agency coordination. The research method used was qualitative through interviews, field observations, and literature studies. The results of the study show that KSOP plays a significant role in four main aspects, namely: Licensing and ship administration services through the digitization of Inaportnet, which speeds up bureaucratic processes and increases transparency; mooring arrangements and smooth ship traffic, which reduce waiting times and increase turn-around time; effective sailing safety supervision and technical inspections, which prevent incidents and increase operational safety; and collaboration with stakeholders through cross-sector coordination that facilitates the distribution of goods. In general, the contribution of KSOP Talang Duku has been proven to help reduce logistics costs, accelerate distribution flows, and strengthen the competitiveness of river ports. However, the sustainability of KSOP's effectiveness is highly dependent on improvements in infrastructure, the quality of human resources, and cross-sector integration in the national logistics system.